Hubungan Tingkat Perolehan Sumber Informasi Dengan Tingkat Pengetahuan Remaja Tentang HIV/AIDS Di SMK Negeri 1 Pandak Bantul - Adud, Adud; Desi Ekawati; Wiwin Hindriyawati; Anugerah Destia Trisetyaningsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Data from the Yogyakarta Health Office, the number of new HIV cases increased in 2022, from 327 people to 916 during the 2016-2022 period, there were 2,050 AIDS cases and 6,784 HIV/AIDS cases. Bantul Regency is second only to Sleman Regency with 160 new AIDS cases dominated by the 25-29 year old and 15-19 year old age groups. This study aims to determine the relationship between the level of acquisition of information sources with the level of knowledge of adolescents about HIV/AIDS at SMK Negeri 1 Pandak Bantul. Using quantitative analytic survey method with cross sectional approach. Stratified random sampling technique. The sample size was 90 respondents at SMK Negeri 1 Pandak Bantul. Data were analyzed univariately and bivariately using the Chi-Square test. The results stated that the characteristics of the respondents were mostly 17 years old,39 (43.3%) and dominated by women 75 (83.3%). The majority of respondents' level of information source acquisition was in the good category, 74 (82.2%). The level of knowledge of respondents about HIV/AIDS was in the good category, 83 (92.2%) respondents. The result of the Chi-Square test calculated 1.641, where x 2 < 5.991 indicates that there is no significant relationship between the level of acquisition of information sources with the level of knowledge of adolescents about HIV/AIDS. The conclusion is that there is no significant relationship between the level of acquisition of information sources with the level of knowledge of adolescents about HIV/AIDS at SMK Negeri 1 Pandak Bantul.